Anticipated death in New Zealand school communities. (Kairaranga, 2008)
Few resources seem to be available to support school communities that have a child whose death is anticipated. The present article draws on the experiences of school staff and special education employees who have been involved in New Zealand school communities where a child was terminally ill and died These experiences could help other school communities to provide optimal support and avoid pitfalls Schools could use this article to develop a plan tofit their own unique situation.